The Validation and Reliability of the Food and Health Questionnaire to Assess Health and Nutrition Knowledge. Issue 1 (March 2022) - Alhaj, Omar A.; Al-Sayyed, Hiba F.; Charouf, Ola M.; Jahrami, Haitham; Morris, Keith
Purpose: This study aimed to translate and test the content validity and reliability of an English questionnaire used in the American food and health survey. Methods: The questionnaire was developed using 6 stages, then examined for test–retest. A total of 672 participants were recruited for validation and reliability. Validity test was performed using a correlation coefficient to measure the linear correlation between 2 questions at one given time. Moreover, the Kaiser-Meyer-Olkin, Measure of Sampling Adequacy, and Bartlett's Test of Sphericity were performed to statistically determine the suitability for conducting exploratory factor analysis. Furthermore, reliability tests using Cronbach α was used to estimate the reliability coefficient properties of the translated scale. Finally, the most important correlated questions was plotted using a color-coded correlogram. Results: The test–retest reliability of all tested items was significantly correlated. The reliability test for all questions was 0.9. The cross-correlation test showed that all questions of the translated questionnaire were correlated significantly ( P < .05) indicating reliability of the questionnaire. Conclusion: The tested questionnaire is applicable and may be used in population-based studies to raise awareness regarding health, food consumption, nutrition, and food safety among people in Jordan and/or other Arab countries.